Determination of outdoor design parameters for arid zone-Waddan Libya: A case study - Masheiti, Salah; ballil, Ahmed; Bodalal, Awad (Libyan Journal of Science &Technology, 2022)
Incorrect selection of outdoor parameters, such as temperature, can be costly when cooling and heating demand of domestic dwellings are considered. If extreme weather conditions are taken, uneconomical design and oversizing may result. In this paper prevailing weather data for Dry Bulb Temperature (DBT) and Relative Humidity (RH), for one year, were collected and graphically presented and analysed. The data were collected from a weather station situated at a Saharan Desert Oasis in the North East of Fezzan region of South West of Libya (Waddan city) for one complete year of 2007. The detailed analysis, which was carried out using Microsoft Excel software, has revealed that the dry bulb temperature range of 22 to 40C and the relative humidity of 44% were suggested to be the outdoor design parameters that should be considered during design or selection of thermal systems in arid-zones. It has been also observed from the analysis of relative humidity curves that, during the day, the weather conditions of humid arid zone areas were completely different from the conditions at the night. Very humid and warm during the day and lowto-moderate humid and cold during the night for the entire year.